The implementation of RFID in aviation industry: a preliminary study on the technological aspect / Shahrul Ahmad Shah ...[et al.] - Ahmad Shah, Shahrul; Harun, Mohd Khir; Mokhtar, Ahmad Zahir; Alias, Ahmad Jais; Sufian, Maz Amir (2006)
RFID (Radio Frequency Identification) is a new technology that is starting to have significant impact in aerospace/aviation industry in the world. It has become an increasingly recognized technology with its strong tracking and tracing ability at a much greater level of accuracy, real-time and provides more value at each step in its application. With the aerospace/aviation environments becoming more and more information-intensive, and their information systems are sharing the fundamental information of assuming rather than knowing where and what things are, RFID technology provides the solution for closing the gap between the physical flow of materials and the information flow in the production system. This paper is a preliminary report of an ongoing study and research on the technological aspect of the RFID implementation, focusing in the aviation MRO (Maintenance Repair and Overhaul) industry in Malaysia. This research will also provide a good path for future developments of RFID in any other industry.